CAN THE RS2234246 POLYMORPHISM IN THE TREM-1 GENE BE RELATED TO THE CLINICAL COURSE IN INDIVIDUALS INFECTED WITH PLASMODIUM VIVAX IN AN ENDEMIC AREA OF THE BRAZILIAN AMAZON? - Marcelo Cerilo-Filho; Myrela Conceição Santos de Jesus; Rubens A.O. Menezes; Marrara Pereira Sampaio; José Rodrigo S. Silva; Tatiana R. Moura; Luciane M. Storti-Melo; Ricardo Luiz Dantas Machado (Brazilian Journal of Infectious Diseases)
Introduction: Plasmodium vivax is the most widely distributed species of malaria in the world. In Brazil, this parasite is responsible for around 90% of cases. Infections caused by P. vivax can generate a variety of symptoms, such as fever, chills, headache, nausea, vomiting and anemia. The immune response directly influences the individual's clinical evolution. The TREM-1 receptor is an important molecule that acts by recognizing the pathogen and amplifying inflammation. Polymorphisms in the gene encoding this protein have been linked to the severity of malaria. Objective: We investigated the association between the SNP rs2234246 (C>T) in the TREM-1 gene and the development of nausea and vomiting in individuals infected with P. vivax in an area of the Brazilian Amazon. Methodology: We analyzed 76 patients with a microscopic and molecular diagnosis of P. vivax and 114 controls from the municipality of Oiapoque in Amapá state, Brazil, on the border with French Guiana. The clinical signs of the individuals were assessed by a nurse. Genomic DNA was extracted from blood samples and the SNP rs2234246 was genotyped by qPCR. The occurrence of nausea and vomiting symptoms was adjusted for the SNP using Logistic Regression. Variables such as: occurrence of anemia, gender, age, length of residence in the study area, number of previous episodes of malaria and period of the last malaria were inserted as adjustment variables for the logistic regression. All analysis was carried out with a 5% significance level. Results: Among the 76 patients, 44.7% reported experiencing nausea and vomiting. As for SNP rs2234246 genotyping, CC = 15, CT = 42 and TT = 19. In the association between the SNP and symptoms, it was observed that infected individuals with the TT mutant genotype for the TREM-1 rs2234246 C>T SNP were 90% less likely (OR = 0.1; 95% CI = 0.0 - 0.6; p = 0.013) to develop nausea and vomiting than wild-type CC individuals. The reduced risk of developing these symptoms may provide relevant insight into the human parasite-host relationship in the population studied, which may suggest a possible protective role for the homozygous mutant allele (TT). Case highlighting characteristics malaria vivax infection, necessitating close clinical and laboratory correlation. Conclusion: Our results aim to help the global public develop a comprehensive understanding of malaria in Brazilian-French Guiana, thereby contributing to malaria control and elimination. Keywords: Immunological Factors, Malaria, Polymorphism, Genetic, Signs and Symptoms. Conflicts of interest: There was no conflicts of interest. Ethics and financing: Declarations of interest: None.